Measuring Financial Reporting Quality in Private Banks: A Comparative Study Between Banks Adopted International Accounting Standards and Banks Adopted Local Accounting Standards - ahmed dawed, Samia; ahmed ghareeb, reem (Finance and Business Economies Review, 2023)
This research examines financial reporting quality in the banking sector of developing countries. through testing whether managers manipulate estimated components of Loan Loss Provision (LLP). And since accounting estimation process depends on professional judgment and flexibility granted by accounting standards. This research hypothesizes that the adoption of international accounting standards improves financial reporting quality in developing countries by limiting earnings management behavior. However, the results showed that financial reports based on local accounting standards are better than financial reports based on international accounting standards. The findings were discussed. Some recommendations and suggestions were provided